Factors That Influence The Intention To Implement Sak Indonesia For Emkm In Presenting Financial Statements (Case Study On Umkm In Sematang Borang Sub-District) - Sari, Annisa Julia; Vegirawati, Titin; Ningsih, Endang Kusdiah (Universitas Dehasen Bengkulu, 2025)
This study aims to identify and analyze the factors that influence the intention of Micro, Small, and Medium Enterprises (MSMEs) to implement Indonesian Financial Accounting Standards (SAK) for Micro, Small, and Medium Entities (EMKMs). This study uses a quantitative approach with data analysis based on Structural Equation Modeling–Partial Least Square (SEM-PLS). The sample size was determined based on the Isaac and Michael table, and respondents were selected according to the established criteria. Data was collected through the distribution of questionnaires to business owners who were the subjects of the study. The analysis results indicate that the variables of performance expectations, social influence, and supportive conditions have a positive and significant effect on the intention to implement EMKM FAS. Conversely, the variable of business expectations does not show a significant effect on this intention. These findings imply that in encouraging the implementation of SAK EMKM among MSMEs, it is important to improve perceptions of the benefits of implementation, strengthen social support, and create a supportive environment, rather than just emphasizing the effort or workload required.